Formation and transformation of glands and muscle tissue in the prostate of human fetuses. - Piatsko, I. A.; Usovich, A. K. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. At the present time in the literature there is conflicting information about the course of the processes of human prostate morphogenesis. A more thorough study of the processes of morphogenesis in the pathologically unchanged prostate can facilitate understanding of the occurrence of atypical forms of glands and muscle bundles. Objective. To study in the human prostate the formation and transformation of glands and muscle tissue. Materials and methods. A morphometric study was performed on 19 prostate fetuses from 14 to 40 weeks of intrauterine development. Results. It was established that the transformation of epithelial buds into glandular tubules is not accompanied by an increase in their area, since the formation of ta lumen occurs by apoptosis. The main stages of the transformation of epithelial strands into typical alveolar-tubular glands are traced. At this insignificant increase in the specific area of the glandular parenchyma in the organ, the transformation of the developing glands occurs mainly due to their canalization (the specific area of the gland enlarges increases 3.8 times - p <0.05). Conclusions. Transformation of prostate glands in the prenatal period occurs in a certain sequence: the formation of epithelial buds, their canalization by apoptosis with the formation of epithelial ducts and prostatic ducts and the formation of end pieces of prostate glands from these ducts. In prenatal periods, the structure and orientation of smooth muscle bundles around the glands can not provide evacuation of the contents of the prostate glands.